2020
DOI: 10.1088/1361-665x/ab6076
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of bolt connection using a single piezoceramic transducer and ultrasonic coda wave energy with the consideration of the piezoceramic aging effect

Abstract: Smart Materials and Structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Experimental results obtained from the three different specimens demonstrated that the method can quantify bolt looseness with an accuracy of more than 95.78%. Single monitoring indices, such as the peak value of a time reversal signal (Tao et al, 2016) and normalized coda wave energy (Hei et al, 2020), are unable to provide true quantitative monitoring due to the dispersion of the single indices. On the other hand, through powerful feature extraction and classification abilities, the trained 1DCNN model can quantitatively monitor the state of bolt looseness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results obtained from the three different specimens demonstrated that the method can quantify bolt looseness with an accuracy of more than 95.78%. Single monitoring indices, such as the peak value of a time reversal signal (Tao et al, 2016) and normalized coda wave energy (Hei et al, 2020), are unable to provide true quantitative monitoring due to the dispersion of the single indices. On the other hand, through powerful feature extraction and classification abilities, the trained 1DCNN model can quantitatively monitor the state of bolt looseness.…”
Section: Discussionmentioning
confidence: 99%
“…A concept of "smart washers" was proposed to monitor bolt looseness through a normalized wavelet energy index . Taking into account the aging of piezoceramic materials, the tracking of normalized coda wave energy helped to monitor the tightness of a single bolt (Hei et al, 2020). However, these methods are inadequate for conducting quantitative monitoring because they fail to accurately and quantitatively correlate bolt looseness states with a single monitoring index.…”
Section: Introductionmentioning
confidence: 99%
“…Past researches have shown that the wavelet package-based energy is sensitive to cracks in concrete structures [62,63]. When the stress wave propagates inside the prestressed curved tendon duct, due to the duct grouting defects, reflection attenuation [64,65], scattering attenuation, and absorption attenuation of stress wave will result in a large loss of stress wave energy. Therefore, the defect degree of the curved tendon duct can be judged according to the change of energy.…”
Section: Wavelet Packet-based Energy Methodsmentioning
confidence: 99%
“…Traditional ultrasonic techniques have been investigated for axial force monitoring in bolts [ 5 , 6 ]. Transmittance [ 7 ], impedance [ 8 ], and coda wave [ 9 ] methods have also been investigated.…”
Section: Introductionmentioning
confidence: 99%